PENGARUH LINGKUNGAN LAPAS TERHADAP PERKEMBANGAN ANAK : PERSPEKTIF PSIKOLOGIS DAN SOSIAL - Mitro Subroto; Rizq Adyatma Sinulingga (Universitas Wiralodra, 2025)
his study evaluates the impact of the prison environment on children's development from a psychological and social perspective. The prison environment, with its stress and separation from family, leads to emotional and cognitive impairments, including difficulty sleeping, concentration, and social skills. Children in prisons also face social stigma and isolation, as well as family disconnections, which disrupt their sense of security. Psychological and social support, such as therapy and family programs, are essential to overcome these impacts. This research highlights the need for collaboration between governments, social institutions, and communities to provide effective interventions for the optimal well-being and development of children in prisons.